THE EFFECT OF THE QUALITY OF THE SYSTEM AND INFORMATION QUALITY ON THE SATISFACTION OF THE USER OF THE APLICATION PRODUCT (SAP) WITH PERCEIVED USEFULNESS AS A MODERATING VARIABLES IN THE NATIONAL ELECTRICITY COMPANY - Aulia, Risa (Asosiasi Dosen Akuntansi Indonesia, 2018)
The Objective of the research was to test and analyze the influence of the Quality System and Information Quality on the Last Users' Satisfaction with System Application Product (SAP) with Perceived Usefulness as moderating variable, whether the variables of Quality System and Information Quality simultaneously and partially had the Last Users 'Satisfaction with SAP, and Perceived Usefulness as moderating variable influenced by the correlation of Quality System and Information Quality with the Last Users' Satisfaction with SAP.The research used causal method.Primary data were gathered by the distributing questionnaire to the employees of National Electricity Company, the Sumatra Power Plant Development Unit.The population was 207 employees, and 42 of them were used as the samples, taken by using purposive sampling technique.The result of the research showed that, partially, the System Quality had positive and significant influence on the Last Users 'Satisfaction with SAP, while the Information Quality had Last Users' Satisfaction with SAP.Simultaneously, Quality System and Information Quality have Last Users' significant influence with SAP, while Perceived Usefulness was not moderating variable